STRATEGI PENINGKATAN KUNJUNGAN PASIEN MELALUI PENERAPAN SOP 5S DI UNIT RAWAT JALAN RUMAH SAKIT ISLAM METRO - Dita Tri Sekarwati; Putra , Yogi Catur; Aprilianingsih, Maya (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction: service quality and patient satisfaction are key indicators of hospital performance. islamic hospital metro experienced a 15.72% decrease in outpatient visits during the first half of 2025. Method: this research used an observational descriptive approach involving field observations, interviews, and documentation. priority problems and solutions were determined using the USG and fishbone analysis. Results : the decline in patient visits was primarily caused by poor non-clinical service, particularly the lack of friendly staff behavior. the solution implemented was the development of a 5s-based service sop (smile, greet, salute, polite, courteous) and educational pamphlets. this approach positively impacted patient satisfaction and improved public reviews. Conclusion: implementing the 5s sop is an effective strategy to enhance service quality, hospital image, and ultimately increase outpatient visits